Occurrence of Cephaleuros in Gorakhpur - Bhargava, K. S.; Joshi, R. D.; , Kamal (Indian Forester, 1966)
In the present study the authors have made an attempt to record sixty hosts of Cephaleuros from Gorakhpur. The alga occurs as epiphytic on the hosts, which are mostly forest trees. As the alga covers the leaf-surface, it hinders the photosynthetic process of the infected plants. In severe case when the foliage are heavily covered with the algal lesions, it may induce rapid defoliation. The wide spread of the disease during rainy season may be due to high relative humidity and less diurnal fluctuation in temperature which provide favourable conditions for the growth of this tropical alga.